Leadership and job performance: relationships with autonomy, intrinsic motivation and engagement - Queiroz, Aldeci Rufino de; Mendonça, Helenides; Soares, Vinícius Nagy (Revista de Administração da UFSM, 2025)
Purpose: This study examines the relationship between engaging leadership and job performance through a mediation and moderation model, incorporating engagement as a mediator and intrinsic motivation and autonomy as moderators. Design/Methodology: A cross-sectional study was conducted involving 425 workers from various economic sectors, predominantly consisting of women (53.6%), individuals with a college degree (64%), and private-sector employees (61.6%), with a mean age of 36.7 years (SD = 10.7) The participants completed the Engaging Leadership, Engagement, Autonomy, Intrinsic Motivation, and Job Performance Scales. Findings: Engagement mediates the relationship between engaging leadership and performance, while autonomy moderates the relationship between engagement and job performance. Originality: Our findings suggest that engagement precedes improvements in job performance, and that workers with high autonomy levels rely less on engagement to achieve high performance. Practically, this study highlights the importance of leaders fostering a healthy organizational environment through practices encouraging communication, mutual support, and continuous encouragement between leaders and employees. This approach signifies a contemporary and innovative leadership style, emphasizing the satisfaction of workers’ basic psychological needs as central to achieving organizational goals effectively and sustainably.